Cemento-ossifying Fibroma of the mandible: A case report with 2 - year follow-up - UĞURLU, FAYSAL (My University, 2019)
Cemento-ossifying fibroma is a benign fibro-osseous lesionin which normal bone is replaced by fibrous tissuecontaining variable amounts of mineralized material. Patientsin the 3rd to 4th decades are most affected, witha high female-to-male ratio. The lesion can attain a hugesize that commonly presents as a progressively growingbehaviour if left untreated. Ossifying fibromas requiremore extensive treatment than other fibro-osseous lesions,such as fibrous dysplasias and osseous dysplasias,because they are true neoplasms. This paper reports acase of a cemento-ossifying fibroma, together with theclinical, radiological, and histopathological features, surgicaltreatment, and findings at the 2-year follow-up.

Semento-ossifiye fibrom; normal kemiğin çeşitli miktarlarda mineralize materyal ihtiva eden fibröz doku ile yer değiştirdiği iyi huylu fibro-osseöz bir lezyondur. Yaşamın sıklıkla 3. ve 4. dekadında etkilenen hastalarda kadınlar erkeklere oranla daha fazla etkilenmektedir. Lezyon eğer tedavi edilmezse genellikle giderek büyüyen bir davranış ortaya koyar ve oldukça geniş boyutlara ulaşabilir. Ossifiye fibromlar, gerçek birer neoplazm oldukları için fibröz displaziler ve osseöz displaziler gibi diğer fibro-osseöz lezyonlara göre daha kapsamlı tedavi gerektirirler. Bu makalede klinik, radyolojik bulguları, histopatolojik özellikleri, cerrahi tedavisi ile birlikte 2 yıl takipli bir semento-ossiyife fibrom olgusu sunulmuştur.
Mandibulada Semento-Ossifiye Fibroma: 2 yıl takipli bir olgu raporu
Keywords: Diş Hekimliği